Efektivitas Penyaluran Pembiayaan Modal Ventura sebagai Alternatif Modal Bagi UMKM - Susiana Susiana; Yunita Yunita (Universitas Syiah Kuala, 2013)
ABSTRACT: This study aims to identify and explain the venture capital financing as an alternative capital for SMEs, constraints faced by SMEs in order to obtain venture capital financing in Banda Aceh. The data consist of primary and secondary data. The primary data are obtained through interviews with PMV (PT Sarana Aceh Ventura) and SMEs which are the PPU of the PMV. While the secondary data obtained through secondary research by studying books or articles as well as legislations relating to venture capital. The research shows that the distribution of venture capital financing in Banda Aceh is not effective as an alternative capital for SMEs. Financing provided by PMV in practice is equal to bank credit. It is not in the form of capital but in the form of loans that have been specified number of installments of principal and interest and late fees. SMEs that are constrained by the guarantee will not get funding from PMV. The Effectiveness of Venture Capital Financing Distribution as an Alternative Capital for UMKM